Rheumatoid arthritis in Jordan: a cross sectional study of disease severity and associated comorbidities - Alawneh KM; Khassawneh BY; Ayesh MH; Smadi M (Dove Medical Press, 2014)
Khaldoon M Alawneh,1 Basheer Y Khassawneh,1 Mahmoud H Ayesh,1 Mahmoud Smadi21Department of Medicine, College of Medicine, King Abdullah University Hospital, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Math and Statistics, College of Science, Jordan University of Science and Technology, Irbid, JordanAbstract: Treating rheumatoid arthritis (RA) to target is advocated using disease activity measures. The impact of RA on the general health status of affected patients in Jordan is not well described. This study reported the severity of RA in Jordan and its association with consequent disabilities and comorbidities. A cross-sectional, observational study was conducted at King Abdullah University Hospital in the north of Jordan. All patients who were diagnosed with RA were included. Patients’ demographics, comorbidities, disease activity score (DAS 28), and clinical disease activity index (CDAI) were collected. Both DAS 28 and CDAI were utilized to categorize RA disease activity. A total of 465 patients with RA were included: 82% were females; mean age ± standard deviation (SD) was 47.62±14.6 years; and mean disease duration ± SD was 6±4.45 years. The mean ± SD for the DAS 28 and CDAI was 5.1±1.5 and 23±14.2, respectively. According to the DAS 28, 51% of the patients were in the high disease activity category and only 5% were in remission. On the other hand, according to the CDAI, 44% were in the high disease activity category and only 1% were in remission. In Jordan, patients with RA have a high severe disease rate and a low remission rate. The disease is often progressive and associated with comorbidities that need to be managed.Keywords: rheumatoid arthritis, DAS 28, CDAI, Middle East, remission, disabilities